The Roles of CircRNAs in Regulating Muscle Development of Livestock Animals - Yang, Zhenguo; He, Tianle; Chen, Qingyun (Frontiers in Cell and Developmental Biology, 2021)
The muscle growth and development of livestock animals is a complex multi-stage process, which is regulated by many factors, especially the genes related to muscle development. Recent studies have shown that circular RNAs (circRNAs) are widely involved in cell proliferation, cell differentiation and body development (including muscle development). However, the research on circRNAs in muscle growth and development of livestock animals is still in its infancy. In this paper, we briefly introduce the discovery, classification, biogenesis, biological function and degradation of circRNAs, and focus on the molecular mechanism and mode of action of circRNAs as a competitive endogenous RNAs in the muscle development of livestock and poultry. In addition, we also discussed the regulatory mechanism of circRNAs on muscle development in livestock in terms of transcription, translation and mRNA. The purpose of this article is to provide a certain basis and theoretical basis for circRNAs in livestock muscle development, to provide new ideas for the development of a new co-expression regulation network, and to lay a foundation for enriching livestock breeding and improving livestock economic traits.